New talitrids from South Africa (Amphipoda, Senticaudata, Talitroidea, Talitridae) with notes on their ecology - Lowry, J.k.; Baldanzi, S. (Zootaxa, 2016)
Based on new talitrid amphipod collections from South Africa one new genus, Capeorchestia gen. nov., and one new species, Africorchestia meridionalis sp. nov., are described and Africorchestia quadrispinosa (K.H. Barnard, 1916) is redescribed. Eorchestia Bousfield, 1984 is redescribed. Based on this redescription Orchestia dassenensis (K.H. Barnard, 1916) is moved to Eorchestia and the Tasmanian species Eorchestia palustris Richardson, 1993 and E. rupestris Richardson, 1993 are moved to Microrchestia Bousfield, 1984. The current knowledge about the ecology of Capeorchestia capensis (Dana, 1853), Africorchestia quadrispinosa and A. meridionalis is summarized.